Hemangiossarcoma na língua de um gato - Gnoatto, Calvin Braga (2020)
Background: Hemangiosarcoma is a primary malignant neoplasm of vascular endothelial cells, common in dogs and uncommon in cats. It is characterized by being aggressive and presenting high metastatic behavior. It corresponds to 0.5% to 2% of all feline neoplasms, with more reports in shorthaired cats aged between 8 and 12.2 years old, with no predisposition for sex or breed. Among the diagnostic methods, histopathological and immunohistochemical exams stand out because they are more accurate, since the result of fine-needle aspiration biopsy is usually hidden by blood contamination. This report aims to describe a case of a hemangiosarcoma in a cat’s tongue. Case: A 9-year-old, female, shorthair cat with a history of weight loss, lethargy, chewing difficulty with the evolution of three months and two-day oral bleeding was attended. Physical examination revealed blood in the oral cavity, enlargement, and darkening of the tongue surface, normalized oral and ocular mucous membranes, estimated dehydration of 7%, a rectal temperature of 38.8OC, and pulmonary and cardiac auscultation without changes. The cat was hospitalized, and euthanasia was elected. Cytological and histopathological exams of the tongue were requested, which revealed a neoplastic proliferation of endothelial cells expanding and replacing the muscular layer of the tongue, forming primitive vascular structures filled with a large number of red blood cells and supported by a delicate fibrovascular stroma. There were moderate anisocytosis and anisocariosis and rare figures of mitosis. Immunohistochemical examination showed the expression of von Willebrand factor, smooth muscle vimentin, and actin in the cytoplasm of neoplastic cells, and negative staining for pancitokeratin. Discussion: According to the results of cytological, histopathological and immunohistochemical examinations, the cat was diagnosed with tongue hemangiosarcoma. The involvement of the tongue in cases of feline hemangiosarcoma is not commonly reported, as the oral cavity is an uncommon site of neoplasm in cats and hemangiossarcoma neoplasm is considered rare in this species. The cytological examination of the patient’s tongue was useful to suggest the diagnosis of sarcoma due to a large number of neoplastic cells present in the sample, and later, because it is more specific, the histopathological examination was performed to find out the origin of the tissue. The definitive diagnosis of Hemangiosarcoma could be confirmed by the alterations found in the histopathological and immunohistochemical exams. The appearance of erythrocytes within tumor vascular channels, the rapid mass development, moderate anisocytosis, anisocariosis, and irregularity of vascular channels, along with the expression of smooth muscle action, excluded the differential diagnosis of hemangioma and lymphangiosarcoma. Due to the ability of the hemangiosarcoma to be a primary or metastatic tumor and the performance of the necropsy examination was not authorized, we could not determinate the primary origin of the tumor. However, we suggest in the present study that the neoplasm is primary of the tongue because there are no skin lesions or alterations in other organs, besides the tongue is not a common site of metastasis. In conclusion, Hemangiosarcoma should be included as a differential diagnosis in cases of tongue neoplasia, although uncommon in felines, and that histopathological and immunohistochemical examinations are indispensable to define an accurate diagnosis.